ECSPLICATION OF CONFLICT AS MOTIVE FORCE OF ACTION IN DRAMATIC NOVELS OF DIASPORA OF THE FIRST HALF OF THE ХХ CENTURY (on materials of works E.Кarpenko, L.Poltava, V.Chaplenko) - Semak, O. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article has the investigation of the correlation of action and conflict based on the material of the dramas of Y.Karpenko, L.Poltava, V.Chaplenko. This approach gives us an opportunity to speak about dramatic action as the motive power of conflict.